Shaking Table Test on Dynamic Response of Bedding Rock Slopes With Weak Structural Plane Under Earthquake - Yang, Changwei; Zhang, Liang; Liu, Yang; Tian, Denghang; Guo, Xueyan; Liu, Yang (Frontiers in Physics, 2020)
According to the potential disaster points of bedding rock slopes with weak structural plane in the mountainous areas of southwest China, the seismic simulation shaking table test is designed and carried out to study the seismic dynamic response of bedding rock slopes under different seismic wave types, frequencies and amplitudes. The results show that before the failure, the bedding rock slopes presents obvious "elevation effect" and "surface effect" under the action of different intensities of Wolong earthquake wave. With the increase of the amplitude value of the input earthquake, the elevation effect and the surface effect gradually weaken. When the seismic amplitude reaches 0.9g, the bedding rock slopes begins to lose stability. Because of the existence of the weak structural plane, the movement inconsistency of the slopes on both sides is enhanced, and the slope is gradually separated from the main body of the slope, resulting in the instability and failure of the slope, which is manifested in the significant increase of the difference of the amplification coefficient of the peak acceleration on both sides of the structural plane. At the same time, the influence of the seismic wave type on the elevation amplification effect of the peak acceleration of the rock slope is mainly reflected in the predominant frequency of the seismic wave and the natural vibration of the slope In terms of frequency difference, the predominant frequency of El Centro seismic wave is closer to the first natural frequency of the slope model, resulting in resonance phenomenon, which leads to the more significant effect of peak acceleration elevation amplification. By analyzing the instability process of bedding rock slopes, it can be found that the instability mechanism of the slope is mainly divided into two stages: the formation of sliding shear plane and the whole instability of the slop.